THE RELATIONSHIP BETWEEN INCOME AND ACCESS WITH PAYMENT REGULATIONS OF HEALTH INSURANCE FOR SELF-FINANCING MEMBERS IN PUUWATU PRIMARY HEALTH CARE CENTRE IN KENDARI CITY: HEALTH INSURANCE FOR SELF-FINANCING MEMBERS - Sri Mulyani (STIKes Mandala Waluya Kendari, 2020)
Background: The number of Health Insurance members in Puuwatu Primary Health Care Centre in 2016 contributed 204 people with arrears of Self-Financing In Health Insurance about 86 people (42.2%) and in 2017 driving membership was 246 people based on data up to June 2017 that arrears contacted 112 people (45, 5%). The purpose of the study was to study the relationship of knowledge and attitudes with regular pay in Self-Financing In Health Insurance members in Puuwatu Primary Health Care Centre, Kendari City. Methods: This type of quantitative research with a cross-sectional study design. The population of all Self-Financing In Health Insurance members who work and have income in Puuwatu Primary Health Care Centre receives 106 people. Samples were taken by the Proportional Random Sampling technique taken 84 people. Results: The statistical test results use the Chi-square test, receive a value of ? <a (0,000 <0.05) on income and improve efficiency, determine there is a relationship between income and access to the regular payment of contributions to participants in the Self-Financing In Health Insurance. Suggestions for in Puuwatu Primary Health Care Centre in Kendari City to provide counselling about the number of premium contributions, ownership of an account from a Bank approved by BPJS Health, access location for premium payment of Self-Financing In Health Insurance. Conclusion: Based on the results of the study, it can be concluded that there is a relationship between income and access to the regular payment of contributions from Self-Financing In Health Insurance members.